Cognitive Algebra Underlying Special Education Teachers’ and Psychology Students’ Attitudes Towards School Inclusion of People with Intellectual Disability (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Attitudes towards regular school inclusion of people with intellectual disabilities (ID) are affected by factors such as disability severity, educational level, and teacher experience. Nevertheless, the ways that teachers integrate these factors to form inclusion judgments remains unclear. The current paper explores what systematic cognitive algebra rules are used to cognitively integrate this set of inclusion factors by special education teachers and psychology students. To do so, 469 special education teachers and psychology students were asked to take part in two experimental cognitive algebra studies. In each study, participants had to read a set of school inclusion scenarios and rate the probability that a scenario actor with ID could be successfully integrated into a regular school program. To this purpose, factor effects on successful school inclusion and ID related to individuality, situational aspects, and contextual considerations (e.g., school environment, grade level taught) were explored. Results suggested that participants showed attitudes to school inclusion ranking from light to moderate positive values. Situational factors, as well as context factors, were judged to be more significant than other factors in elementary education. These factors were integrated by following a cognitive summative rule. Overall, judgment for successful school inclusion follows a summative rule to integrate sources of information. This rule is maintained irrespective of the disability under consideration. However, valuation of each source of information does depend on the type of the current study sample. Implications of these results for inclusion of people with disabilities in regular schools are discussed in this paper.